Contents of anti-nutritional factors in grains of new sorghum cultivars harvested at two vegetative stages and in two seasons of the year - Rodríguez, Janhad L.; Lima, R.; Marrero, L. I.; Castro, A.; Hoedtke, Sandra; Bindelle, J. (Cuban Journal of Agricultural Science, 2016)
Randomly selected grain samples from new sorghum cultivars (CIAP MC-04-12 and CIAP 132-05) harvested in different seasons of the year and at different vegetative stages in 2011 and 2012, were used for determining the contents of phenolic compounds (condensed tannins, total phenols, non-tannin phenols and tannin phenols), β-glucans, phytic acids and cyanogenic glucoside. Results demonstrated that the sorghum cultivar, the vegetative stage and the harvesting season of the grain influenced on the studied concentrations of anti-nutritional factors (ANFs). Tannin phenols in the grains were from 2.6 (CIAP MC-04-12) to 2.8 (CIAP 132R-05) times higher in the dry season regarding the rainy period. Condensed tannin concentrations represented 87 % of the tannin phenols, while the concentrations of β-glucans were from 2.7 to 4.8 times higher (P < 0.001) in the treatments based on CIAP 132R-05 than on those of CIAP MC-04-12. It is concluded that the two cultivars studied are low in all ANFs. This suggests a low effect of these ANFs on nutrient digestibility, energetic content and productive performance of monogastric animals receiving diets in which the grains of these cultivars are the main energy source. Key words: sorghum, anti-nutritional factors, grain vegetative stage